Micro Financing Optimalization Strategy for MSMEs Development (Case Study at Kabupaten Bogor, Indonesia) - Ana Yuliana Jasuni; Muhammad Firdaus; Bunasor Sanim (Indonesian Journal of Business and Entrepreneurship (IJBE), 2018)
MSMEs have a great number of important roles in the economy of a country and should be developed and empowered. The main thing needed in the effort to boost the performance of MSME is support in terms of business funding. The impact of microfinance should be optimized through the appropriate strategies of all parties involved. Through appropriate microfinance strategies, MSMEs are expected to experience significant growth. The purpose of this research is to identify factors influencing access of micro finance and, impact of micro financing and to formulate strategy in optimizing microfinance for MSMEs in Bogor Regency. The primary data obtained from the owners of MSMEs of bag and footwear industries was were analyzed using logistic regression and rank test marked Wilcoxon. The primary data from the experts were analyzed using AHP method. The results showed that the factors that influence access to microfinance are monthly profits, total assets and savings access. Microfinance has a positive impact on almost all aspects of MSME performance. The right strategy to optimize microfinance is the CSR partnership financing program.Keywords: AHP, micro financing, MSMEs, Wilcoxon